Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1139/f03-008
|View full text |Cite
|
Sign up to set email alerts
|

pH 6 as the threshold to use in critical load modeling for zooplankton community change with acidification in lakes of south-central Ontario: accounting for morphometry and geography

Abstract: Identifying thresholds of biotic community change along stressor gradients may be useful to both ecologists and lake managers; however, there are several weaknesses in the thresholds that have been identified for zooplankton communities along acidity gradients. The thresholds are often based on a single species even though pH sensitivities vary among species. They often measure changes in species occurrences, though abundances may be a more responsive indicator of damage. Their identification may be confounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…Daphnia taxa are rare in lakes with pH <6.0 (Keller et al 1990;Havens et al 1993). A study specific to south-central Ontario identified pH 6.0 as the threshold for maximal community change when considering species richness and abundance (Holt et al 2003). Similarly, we found a significant pH threshold of approximately 6.0, with larger mean cladoceran size above this threshold.…”
Section: Discussionsupporting
confidence: 63%
“…Daphnia taxa are rare in lakes with pH <6.0 (Keller et al 1990;Havens et al 1993). A study specific to south-central Ontario identified pH 6.0 as the threshold for maximal community change when considering species richness and abundance (Holt et al 2003). Similarly, we found a significant pH threshold of approximately 6.0, with larger mean cladoceran size above this threshold.…”
Section: Discussionsupporting
confidence: 63%
“…Aside from resource limitation, our analyses also provide evidence that pH can drive species distributions, as it has the highest relative contribution value for both the entire zooplankton metacommunity and for the rotifer metacommunity. The dominance of pH suggests that zooplankton differ in their environmental tolerance ranges for pH, a finding noted elsewhere (Holt et al 2003), which has implications for community composition under the threat of lake acidification. Further, the impact of pH may also include the impact of other variables, as pH is often correlated with other water quality metrics such as calcium (Ca), dissolved organic carbon (DOC), and total organic phosphorus (Jeziorski et al 2012).…”
Section: Discussionmentioning
confidence: 59%
“…The study lakes are a subset of a 300 lake survey conducted by the Canadian Aquatic Invasive Species Network during the summer of 2006 (CAISN; Cairns et al 2006); the survey included determination of a variety of chemical variables from an epilimnetic water sample collected from the deepest point of each lake basin. The 36 lakes of our study were selected a priori from the CAISN dataset to be evenly distributed about two potential environmental thresholds, Ca = 1.5 mg L -1 (Ashforth and Yan 2008) and pH = 6 (Holt et al 2003). The four groups are referred to as: Low Ca/Low pH; High Ca/Low pH; High Ca/High pH; Low Ca/ High pH (Fig.…”
Section: Site Selectionmentioning
confidence: 99%
“…Furthermore, in previous studies only a small number of lakes below the critical threshold of 1.5 mg L -1 were included. Here we investigate how crustacean zooplankton communities differ along a narrow Ca gradient (1.0-3.1 mg L -1 ) using paleolimnological techniques to test the following hypotheses: (1) that the laboratory threshold response of D. pulex (at 1.5 mg L -1 Ca) can be observed within crustacean zooplankton sedimentary assemblages from a spatial dataset, among either the daphniid remains and/or the greater zooplankton community, and (2) that the impacts of Ca deficiency can be distinguished from those of low pH waters (significant differences have been observed among crustacean zooplankton communities above and below pH 6.0; Holt et al 2003), in order to assess whether these two effects can be separated, as they are often intercorrelated.…”
Section: Introductionmentioning
confidence: 99%